Small Vessel Disease - Hakim, Antoine M. (Frontiers in Neurology, 2019)
Small vessel disease (SVD) refers to conditions where damage to arterioles and capillaries is predominant, leading to reduced or interrupted perfusion of the affected organ. Data suggest that when this condition is evident in any organ, it is already systemic in its occurrence and consequences. SVD affects primarily organs that receive significant portions of cardiac output such as the brain, the kidney, and the retina. Thus, SVD is a major etiologic cause in debilitating conditions such as renal failure, blindness, lacunar infarcts, and dementia. The factors that lead to this devastating condition include all the known vascular risk factors when they are not strictly controlled, but lifestyles that include sedentary existence, obesity and poor sleep patterns are also recognized drivers of SVD. In addition, depression is now recognized as a vascular risk factor. Inflammation is a mediator of SVD, but it is not known which factor(s) predominate in its etiology. This article emphasizes the need for more investigations to define this link further and suggests clinical and societal responses that might reduce the major impacts of this condition on populations. Keywords: SVD, vascular risk factors, inflammation, dementia, lifestyle.